Radial velocity confirmation of a hot super-Neptune discovered by TESS with a warm Saturn–mass companion. Issue 4 (16th December 2022) - Knudstrup, E; Gandolfi, D; Nowak, G; Persson, C M; Furlan, E; Livingston, J; Matthews, E; Lundkvist, M S; Winther, M L; Rørsted, J L; Albrecht, S H; Goffo, E; et al.
ABSTRACT: We report the discovery and confirmation of the planetary system TOI-1288. This late G dwarf harbours two planets: TOI-1288 b and TOI-1288 c. We combine TESS space-borne and ground-based transit photometry with HARPS-N and HIRES high-precision Doppler measurements, which we use to constrain the masses of both planets in the system and the radius of planet b. TOI-1288 b has a period of 2.699835^+0.000004_-0.000003 d, a radius of 5.24 ± 0.09 R⊕, and a mass of 42 ± 3 M⊕, making this planet a hot transiting super-Neptune situated right in the Neptunian desert. This desert refers to a paucity of Neptune-sized planets on short period orbits. Our 2.4-yr-long Doppler monitoring of TOI-1288 revealed the presence of a Saturn–mass planet on a moderately eccentric orbit (0.13^+0.07_-0.09 ) with a minimum mass of 84 ± 7 M⊕ and a period of 443^+11_-13 d. The five sectors worth of TESS data do not cover our expected mid-transit time for TOI-1288 c, and we do not detect a transit for this planet in these sectors.